Autologous hematopoietic bone marrow transplantation to treat multiple myeloma: the experience of the Bahia Portuguese Hospital bone marrow transplant unit - Pallotta, Ronald; Lima, Denize Ferreira; Santo, Thyago Monteiro do Espírito (Brazilian Journal of Transplantation, 2006)
Purposes: Based on the heterogeneous distribution of transplantation centers in Brazil, the authors describe their experience treating multiple myeloma in a Northeast bone marrow transplant unit. Methods: From September 2001 to September 2006, 35 autologous transplants for patients with myeloma were performed and analyzed at the Bahia's Portuguese Hospital. Results: There was a prevalence of females (1.5:1) and Caucasians (1.3:1). The median age at the diagnosis was 54, the major part IgG (68.6%) secretes and presenting stage IIIA (88.6 %). The indication for the procedure was consolidation of the initially attained remission by chemotherapy (54.3%) or salvage for refractory disease (45.7%). The overall survival was of 74.76%, the disease-free survival was 60.75%, and the mortality rate was 5.72% in the first 100 days. Results also showed that patients in complete remission had better disease-free survival than those not in remission (72.98% vs 46.25%). Conclusion: It is feasible to conclude that results showed to be similar from the literature, reinforcing the fact that autologous bone marrow transplantation is fundamental in the therapeutic strategy against multiple myeloma, and it is available in the Northeast region of Brazil.